Meningkatkan Kemampuan Menulis Mahasiswa Prodi BPI STIT Al-Urwatul Wutsqo Melalui Pelatihan Penulisan Artikel - Mustofa, Ali; Budiyono, Ahmad; Khoulita, Ikfi; Hakim, Arif Rahman; Wijono, Hani Adi (Lembaga Penelitian, Penerbitan dan pengabdian kepada masyarakat (LP3M) STIT Al-Urwatul Wutsqo Jombang., 2025)
Writing skills are one of the most important basic skills that students must possess, both in academic and professional contexts. Writing is not just about expressing ideas, but also a means of critical thinking, logical argumentation, and systematic communication of ideas in accordance with the rules of good and correct language. Unfortunately, the reality on the ground shows that many students still struggle to produce well-structured, coherent writing with depth of analysis. This situation certainly poses a challenge for universities in preparing graduates who are not only theoretically competent but also able to communicate their ideas through writing. To address these issues, the Student Creativity Programme (PKM) was established with the aim of improving students' writing skills through a range of integrated activities. The main activities include academic writing training, creative writing workshops, and intensive mentoring by experienced mentors. The programme's implementation method emphasises a participatory approach, hands-on practice, and continuous evaluation that focuses on the participants' writing outcomes. Program outcomes demonstrate significant improvements in writing structure, idea development, and language accuracy. Students also appear more confident in producing written works, both scientific and non-scientific. Thus, this programme can serve as a strategic model for the sustainable and practical development of students' writing skills in higher education.